Association of cortical thickness with age of onset in first-episode, drug-naïve major depression. Issue 16 (6th November 2019) - Shen, Zonglin; Jiang, Hongyan; Cheng, Yuqi; Ye, Jing; Lu, Yi; Zhou, Cong; Li, Na; Dai, Nan; He, Mengxin; Xu, Xiufeng
Abstract : Objective: We previously showed differences in brain grey matter volume changes between patients with early-onset adult depression (EOD) and late-onset adult depression (LOD). Here, we aim to identify whether cortical thickness (CT) is affected by the age of onset in patients with depression. Methods: High-resolution MRI images were obtained for 54 major depressive disorder (MDD) patients with EOD, 58 patients with LOD, 57 young healthy controls (HCs), and 58 aged HCs. Depression severity was assessed using the Hamilton Depression Rating Scale 17-item (HDRS17 ). Associations between CT of patients and clinical scores were analyzed. Results: There was a significant main effect of diagnosis for the left rostal anterior cingulate (rACC), right inferior temporal, right lateral orbitofrontal cortex (lOFC), and bilateral pericalcarine. A remarkable onset age-group effect on CT was observed in the rACC and bilateral caudal anterior cingulate (cACC). The diagnosis-by-onset age interaction effect was found in bilateral rACC and right lOFC. Thinning CT in bilateral rACC was observed in EOD patients compared to young HCs. Compared to older HCs, thicker CT in lOFC was seen in the LOD patient group. Compared with the LOD group, the EOD group showed cortical thinning of the right cACC and posterior cingulate cortex (PCC). There were no significant associations between CT in right cACC or PCC with symptom severity or illness duration. Conclusions: MDD patients with different age at onset show distinct CT alterations, suggesting potentially divergent pathological mechanisms of EOD and LOD. Abstract : Supplemental Digital Content is available in the text.